2020
DOI: 10.1093/nar/gkaa290
|View full text |Cite|
|
Sign up to set email alerts
|

Phage T7 DNA mimic protein Ocr is a potent inhibitor of BREX defence

Abstract: BREX (for BacteRiophage EXclusion) is a superfamily of common bacterial and archaeal defence systems active against diverse bacteriophages. While the mechanism of BREX defence is currently unknown, self versus non-self differentiation requires methylation of specific asymmetric sites in host DNA by BrxX (PglX) methyltransferase. Here, we report that T7 bacteriophage Ocr, a DNA mimic protein that protects the phage from the defensive action of type I restriction–modification systems, is also active against BREX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 43 publications
3
59
1
Order By: Relevance
“…3B). Whole genome sequencing of 4 mutants revealed that all of them carried a mutation (T54V) in gene 0.3 which encodes Ocr, an anti-restriction protein that inhibits RM and BREX systems by mimicking the structure of DNA (46,47). In the presence of the system, the transformation efficiency of an Ocr-expressing plasmid was ~100-fold lower than in the absence of the system, while there was no difference when transforming a GFP-encoding plasmid as a control (Fig.…”
Section: Paris Triggers Growth Arrest Upon Sensing An Anti-restrictiomentioning
confidence: 99%
“…3B). Whole genome sequencing of 4 mutants revealed that all of them carried a mutation (T54V) in gene 0.3 which encodes Ocr, an anti-restriction protein that inhibits RM and BREX systems by mimicking the structure of DNA (46,47). In the presence of the system, the transformation efficiency of an Ocr-expressing plasmid was ~100-fold lower than in the absence of the system, while there was no difference when transforming a GFP-encoding plasmid as a control (Fig.…”
Section: Paris Triggers Growth Arrest Upon Sensing An Anti-restrictiomentioning
confidence: 99%
“…For example, the T7 phage encoded Ocr protein is highly acidic and forms a dimer with a bend similar to B-DNA ( 48 , 49 ). Ocr was initially discovered as a Type I restriction enzyme system inhibitor and was more recently shown to inhibit the anti-phage system, BREX ( 50 ). Importantly, systematic mutation of Ocr's acidic residues revealed it to be highly recalcitrant to breakage, similar to AcrIF2*, maintaining inhibitory activity against Type I R-M even with up to 33% of acidic residues mutated ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently another microbial self-defense mechanism, called Bacteriophage Exclusion (BREX) system has been identified [ 71 ]. Although the exact mechanism of action is not well understood, BREX is thought to methylate host DNA asymmetrically to distinguish host DNA from newly acquired phage integration [ 72 ]. The BREX system is usually composed of a core system consisting of proteins containing an ATPase domain, a DNA methyltransferase domain and phosphatase domain [ 71 ].…”
Section: Discussionmentioning
confidence: 99%